2007
DOI: 10.1108/17410400710757169
|View full text |Cite
|
Sign up to set email alerts
|

Measurement and analysis of customer satisfaction: company practices in Spain and Portugal

Abstract: PurposeThe research objective is to analyze the situation and outlook for the future of the measuring and analysis practices used to determine customer satisfaction in 305 ISO 9000‐certified organizations of the Euro‐region Galicia (Spain)‐North of Portugal.Design/methodology/approachThe empirical study was conducted on a random sample of 305 ISO 9000 companies. Data were gathered by personally interviewing those responsible for quality management at the companies.FindingsCertified companies in the Euro‐region… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
2

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Chen & Chen (2007) studied a combination of the data envelopment analysis (DEA) and BSC and another study showed effective quality management through third-generation balanced scorecard (Andersen, Lawrie & Savic, 2004). Other examples are; effective performance measurement for e-business (Hinton & Barnes, 2008), application of research & development organizations using integrated DEA-AHP technique (Jyoti, Banwet & Desmukh, 2008), healthcare capacity measurement (Bamford & Chatziaslan, 2009), implementing a new performance management system within a project-based organization (Cheng, Dainty & Moore, 2006), marketing and performance evaluations in non-profit services (Mano, 2010), measurement and analysis of customer satisfaction (Fernández-González & Prado, 2007), and prioritization of key performance indicators with perspective of an integration of AHP process (Shahin & Mahbod, 2007).…”
Section: Trends In Performance Measuresmentioning
confidence: 99%
“…Chen & Chen (2007) studied a combination of the data envelopment analysis (DEA) and BSC and another study showed effective quality management through third-generation balanced scorecard (Andersen, Lawrie & Savic, 2004). Other examples are; effective performance measurement for e-business (Hinton & Barnes, 2008), application of research & development organizations using integrated DEA-AHP technique (Jyoti, Banwet & Desmukh, 2008), healthcare capacity measurement (Bamford & Chatziaslan, 2009), implementing a new performance management system within a project-based organization (Cheng, Dainty & Moore, 2006), marketing and performance evaluations in non-profit services (Mano, 2010), measurement and analysis of customer satisfaction (Fernández-González & Prado, 2007), and prioritization of key performance indicators with perspective of an integration of AHP process (Shahin & Mahbod, 2007).…”
Section: Trends In Performance Measuresmentioning
confidence: 99%
“…Customer satisfaction is the key to success in many organizations and in other words, determines the success or failure of a company [18]. In the service industry, where the provision of services requires communication and interaction with the customer, the overall satisfaction of customers is based on how they deal with and experience the organization.…”
Section: Introductionmentioning
confidence: 99%
“…In fact customer satisfaction is an introduction to maintain and her/his loyalty (Jamal, 2009) and organizations will be successful that to be able to provide more customer satisfaction than other competitors and suppliers because the customer is the most important asset of any organization (Kazemi & Mohajer, 2009). It can say that customer satisfaction is main factor in the success of many organizations (Fernandez-Gonzalez and Prado, 2007). Customer satisfaction is their evaluation after buying a service that gained from experience of consumption.…”
Section: Introductionmentioning
confidence: 99%